On outer elements of the noncommutative Hp spaces - Yerkex, A.T.; Bekzhan, T.N. (Bulletin of the Karaganda University. Mathematics Series, 2015)
In the article let M be a von Neumann algebra equipped with a faithful normal normalized tracial state t, A be subdiagonal subalgebra of M. We transfer the results of [4] to the case p < 1.